A novel nanobody-based target module for retargeting of T lymphocytes to EGFR-expressing cancer cells via the modular UniCAR platform. (3rd April 2017) - Albert, Susann; Arndt, Claudia; Feldmann, Anja; Bergmann, Ralf; Bachmann, Dominik; Koristka, Stefanie; Ludwig, Florian; Ziller-Walter, Pauline; Kegler, Alexandra; Gärtner, Sebastian; Schmitz, Marc; Ehninger, Armin; et al.
ABSTRACT: Recent treatments of leukemias with chimeric antigen receptor (CAR) expressing T cells underline their impressive therapeutic potential. However, once adoptively transferred into patients, there is little scope left to shut them down after elimination of tumor cells or in case adverse side effects occur. This becomes of special relevance if they are directed against commonly expressed tumor associated antigens (TAAs) such as receptors of the ErbB family. To overcome this limitation, we recently established a modular CAR platform technology termed UniCAR. UniCARs are not directed against TAAs but instead against a unique peptide epitope on engineered recombinant targeting modules (TMs), which guide them to the target. In the absence of a TM UniCAR T cells are inactive. Thus an interruption of any UniCAR activity requires an elimination of unbound TM and the TM complexed with UniCAR T cells. Elimination of the latter one requires a disassembly of the UniCAR-TM complexes. Here, we describe a first nanobody (nb)-based TM directed against EGFR. The novel TM efficiently retargets UniCAR T cells to EGFR positive tumors and mediates highly efficient target-specific and target-dependent tumor cell lysis both in vitro and in vivo . After radiolabeling of the novel TM with 64 Cu and 68 Ga, we analyzed its biodistribution and clearance as well as the stability of the UniCAR-TM complexes. As expected unbound TM is rapidly eliminated while the elimination of the TM complexed with UniCAR T cells is delayed. Nonetheless, we show that UniCAR-TM complexes dissociate in vitro and in vivo in a concentration-dependent manner in line with the concept of a repeated stop and go retargeting of tumor cells via the UniCAR technology.